A COMMON FINDING IN FOVEAL-SPARING EXTENSIVE MACULAR ATROPHY WITH PSEUDODRUSEN IMPLICATES BASAL LAMINAR DEPOSITS. Issue 7 (July 2022) - Fragiotta, Serena; Parravano, Mariacristina; Sacconi, Riccardo; Costanzo, Eliana; Viggiano, Pasquale; Prascina, Francesco; Capuano, Vittorio; Souied, Eric H.; Querques, Giuseppe
Abstract : Extensive macular atrophy with pseudodrusen is preceded by subretinal deposits that progressively disappear with accumulation of subretinal pigment epithelium midreflective material creating an RPE–basal lamina–Bruch membrane separation with a discernible Bruch membrane. These changes may represent thick basal laminar deposits preluding the atrophic changes. Abstract : Purpose: To characterize structural and clinical alterations preceding the diffuse macular atrophy in extensive macular atrophy with pseudodrusen (EMAP) and their evolution toward atrophic changes. Methods: A retrospective chart review was performed of patients with early-onset reticular pseudodrusen (i.e., pre-EMAP) younger than 55 years and EMAP with foveal sparing. Patients were included if they had complete medical records and multimodal imaging. Results: A total of 12 patients were reviewed, of whom 4 of 12 patients (7 eyes) presented a pre-EMAP stage, characterized by the presence of pseudodrusen-like deposits without atrophic changes, while the remaining 8 of 12 patients (10 eyes) exhibited EMAP with foveal sparing (60.1 ± 6.4 years). Subretinal deposits of various stages tended to fade, leaving subretinal pigment epithelium accumulation of hyperreflective material with a physical separation between the retinal pigment epithelium–basal lamina and the Bruch membrane, along with the persistence of hyperreflective material after retinal pigment epithelium loss. These findings preceded atrophy development in a pre-EMAP stage and the EMAP stage with foveal sparing. Conclusion: Our findings presented distinct multimodal imaging features in eyes with reticular pseudodrusen depicting a peculiar phenotype of rapidly progressing atrophy in midlife. The disease spectrum may include other forms of geographic atrophy allied by thickened basal laminar deposits.